Perilaku Spiritual Keluarga dalam Membangun Keharmonisan Rumah Tangga di Desa Tambakrejo - Tongas - Probolinggo - Nur Khosiah (IAIN PAREPARE, 2020)
The family has members consisting of fathers, mothers and children. The family is a major educational place for children. The formation of a child character from the family to it in the family has to be a clear education and strong spiritual behavior in the family so that what is a destination in the family is easy to materialize. In this study aims to know the family's spiritual behavior in establishing household harmony in the village of Tambakrejo Kec. Tongas Kab. Probolinggo. The research methods used are qualitative research methods. Its data collection techniques use observations, interviews and documentaries. Data analysis techniques that are used consist of data reduction, data presentation, withdrawal conclusion. From the results of the study showed that the spiritual behavior of the family in building the harmony of the House of Wringinan village Tambakrejo Kec. Tongas Kab. Probolinggo is with the community Wringinan in building a harmonious household by providing good habituation and good steadness in each member of his family according to Islamic teachings, fill and complement each other, copy understand, understand and believe in each spouse and other members, love and willing to sacrifice to the spouse and other family members.